Efektivitas Pembekalan Keterampilan Narapidana melalui Program Pembinaan Kemandirian di Lembaga Pemasyarakatan Narkotika Klas IIA Jakarta - Muhammad Dimas; Supriyono Sumbogo (Universitas Budi Luhur, 2019)
This thesis discusses the development of independence at the Jakarta Narcotics Prison. By applying the theory of social reintegration, inmates will instill new morals or values in accordance with the wishes of the community. These morals or values are in the form of debriefing skills through self-development. As well as linking it with the guiding principles according to Law Number 12 of 1995 concerning Correctional Services. Obstacles in carrying out independence development are also explained in this study. This study uses a qualitative approach and is presented in descriptive type, whose data collection is done by interviews and literature studies. The results of this study have explained the independence development in the Jakarta Narcotics Prison and its obstacles.